Ionization due to electron and proton precipitation during the August 2011 storm. Issue 4 (9th April 2014) - Huang, Yanshi; Huang, Cheryl Y.; Su, Yi‐Jiun; Deng, Yue; Fang, Xiaohua
Abstract The parameterizations of monoenergetic particle impact ionization in Fang et al. (2010) (Fang2010) and Fang et al. (2013) (Fang2013) are applied to the complex energy spectra measured by DMSP F16 satellite to calculate the ionization rates from electron and ion precipitations for a Northern Hemisphere pass from 0030 UT to 0106 UT on 6 August 2011. Clear enhancement of electron flux is found in the polar cap. The mean electron energy in the polar cap is mostly above 100 eV, while the mean energy in the auroral zone is typically above 1 keV. At the same time, F16 captures a strong Poynting flux enhancement in the polar cap, which is comparable to those in the auroral zone. The particle impact ionization rates using Fang2010 and Fang2013 parameterizations show clear enhancement at F region altitudes mainly due to the low‐energy precipitating electrons, peaking probably in the cusp but also showing enhanced levels throughout most of the polar cap region. The general circulation models (GCMs), National Center for Atmospheric Research Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model, and Global Ionosphere‐Thermosphere Model, using their default empirical formulations of particle impact ionization, do not capture the observed features shown in the total particle ionization rate applying the Fang2010 and Fang2013 parameterizations to DMSP measurements. The difference between GCM simulations and Fang2010 and Fang2013 applied to DMSP data is due to the difference of both the inputs to the models and the parameterization of the ionization rates.